Association of Interleukin-1B and Interleukin-4 Gene Variants with Autoimmune Thyroid Diseases in Tunisian Population. (18th May 2016) - Zaaber, Ines; Mestiri, Souhir; Hammedi, Hounayda; Marmouch, Hela; Mahjoub, Silvia; Tensaout, Besma Bel Hadj Jrad; Said, Khaled
ABSTRACT: Autoimmune thyroid diseases (AITD) including Graves' disease (GD) and Hashimoto's thyroiditis (HT) are complex genetic diseases. Cytokines IL-1B and IL-4 play a role in the pathogenesis of AITD. This study was conducted on Tunisian patients with GD or HT to investigate the association of IL-1B and IL-4 gene polymorphisms with the risk and the prognosis of AITD. A total of 358 healthy controls and 341 patients with AITDs (249 HT and 92 GD) were genotyped for IL-1B +3953C/T and IL-4 intron 3 VNTR polymorphisms. A significant association was found between IL-1B +3953C/T polymorphism and GD or HT, both in the dominant and additive models. The IL-1B +3953T allele was associated with GD ( p = 0.0003, OR = 1.93, CI = 1.34-2.78) and HT ( p = 0.009, OR = 1.43, CI = 1.09-1.88). The IL-4 VNTR polymorphism was associated only with HT risk both in additive ( p = 0.03, OR = 0.31, CI = 0.11-0.86) and recessive ( p = 0.03, OR = 3.04, CI = 1.13-8.17) models. No significant association was found between IL-1B +3953C/T polymorphism and change in the serum concentrations of TSH and FT4 in GD and HT patients. In HT patients, the IL-1B +3953T allele ( p = 0.009, OR = 0.42, CI = 0.22-0.83) and the IL-1B +3953T/T genotype ( p = 0.03, OR = 0.21, CI = 0.04-1.07) were more frequent in the absence than in the presence of an anti-TPO antibody. The proportion of HT patients with the P1P2 genotype of the IL-4 gene was significantly higher in the absence than in the presence of the anti-TPO antibody ( p = 0.04, OR = 0.39, CI = 0.17-0.89). These preliminary results suggest that IL-1B and IL-4 gene polymorphisms may be associated with GD and HT susceptibility and may represent prognostic factors for predicting the severity of HT.